Effectiveness of Ivermectin and Albendazole against Haemonchus contortus in Sheep in West Java, Indonesia - Silvia Puspitasari,; Achmad Farajallah,; Erni Sulistiawati,; Muladno, (Tropical Life Sciences Research, 2016)
Administering a half dose of an anthelmintic is a simple method for detecting resistance in parasites infesting small ruminants. When a single anthelmintic fails in native sheep from Indonesia, a combination of anthelmintics from different chemical classes with different modes of action are administered as an alternative parasite-control strategy. This study compared the anthelmintic efficacy of ivermectin (IVM) and albendazole (ABZ) given either separately as a single dose or half dose or co-administered to sheep naturally infected with Haemonchus contortus. Twelve sheep from Bogor, West Java, Indonesia were divided into the following six treatment groups: half-dose IVM, full-dose IVM, half-dose ABZ, full-dose ABZ, combined IVM + ABZ, and control. The treatment efficacy was determined using the faecal egg count reduction test (FECRT) at day 0 (pre-treatment) and post-treatment at days 7, 14, 21, 28, 35, and 42. The efficacies of half-dose IVM, full-dose IVM, half-dose ABZ, full-dose ABZ, and the combination treatment ranged from –1900% to 100%, 99% to 100%, –167% to 100%, –467% to 89%, and –200% to 100%, respectively. The FECRT for the half-dose IVM, half-dose ABZ, full-dose ABZ showed that H. contortus is resistant to half-dose IVM and ABZ. Full-dose IVM was effective against H. contortus. The combined treatment was more effective against H. contortus than ABZ alone. Memberikan dos separuh antelmintik merupakan suatu kaedah untuk mengesan daya tahan parasit yang menjangkiti haiwan ruminan kecil. Apabila satu antelmintik tidak berkesan dalam kambing biri-biri asal daripada Indonesia, satu kombinasi antelmintik daripada kelas kimia berbeza dengan cara tindakan berbeza diberikan sebagai satu strategi pengawalan parasit alternatif. Kajian ini membezakan kemujaraban antelmintik ivermectin (IVM) dan albendazole (ABZ) yang diberikan secara berasingan ataupun separuh dos ataupun diberikan bersama kepada kambing biri-biri yang dijangkiti secara semula jadi dengan Haemonchus contortus. Dua belas kambing biri-biri daripada Bogor, Jawa Barat, Indonesia telah dibahagikan kepada enam kumpulan rawatan: dos separuh IVM, dos penuh IVM, dos separuh ABZ, dos penuh ABZ, kombinasi IVM + ABZ, dan kawalan. Kemujaraban rawatan telah ditentukan menggunakan ujian pengurangan pengiraan telur tinja (FECRT) pada hari 0 (pra-rawatan) dan pasca-rawatan pada hari-hari 7, 14, 21, 28, 35, dan 42. Kemujaraban separuh dos IVM, dos penuh IVM, dos separuh ABZ, dos penuh ABZ, dan rawatan kombinasi bernilai daripada –1900% hingga 100%, 99% hingga 100%, –167% hingga 100%, –467% hingga 89%, dan –200% hingga 100%, masing-masing. FECRT untuk separuh dos IVM, dos separuh ABZ, dos penuh ABZ menunjukkan bahawa H. contortus mempunyai daya tahan terhadap separuh dos IVM dan ABZ. Dos penuh IVM berkesan terhadap H. contortus. Rawatan kombinasi lebih berkesan terhadap H. contortus berbanding menggunakan ABZ sahaja.